Effect of pedaling cadence on muscle oxygenation during high-intensity cycling until exhaustion: a comparison between untrained subjects and triathletes - Zorgati, H.; Collomp, K.; Boone, J.; Guimard, A.; Buttelli, O.; Mucci, P.; Amiot, V.; Prieur, F. (European Journal of Applied Physiology, 2015)
Purpose: The aim of this study was to compare the muscle oxygenation between trained and untrained subjects during heavy exercise until exhaustion at two extreme pedaling cadences using a NIRS system. Methods: Nine untrained male subjects and nine male competitive triathletes cycled until exhaustion at an intensity corresponding to 90 % of the power output achieved at peak oxygen uptake at 40 and 100 rpm. Gas exchanges were measured breath-by-breath during each exercise. Muscle (de)oxygenation was monitored continuously by near-infrared spectroscopy on the Vastus Lateralis. Results: Muscle deoxygenation (Delta(deoxy)[Hb + Mb], i.e., O2 extraction) and Delta(total)[Hb + Mb] were significantly higher at 40 rpm compared to 100 rpm during the exercise in untrained subjects but not in triathletes (p < 0.05). The time performed until exhaustion was significantly higher at 40 than at 100 rpm in untrained subjects (373 ± 55 vs. 234 ± 37 s, respectively) but not in triathletes (339 ± 69 vs. 325 ± 66 s). Conclusions: These results indicate that high aerobic fitness (1) allows for better regulation between VO2M and QO2M following the change in pedaling cadence, and (2) is the most important factor in the relationship between pedaling cadence and performance.